Bioactive Amines Screening in Four Genotypes of Thermally Processed Cauliflower - Marla Silvia Diamante; Cristine Vanz Borges; Mônica Bartira da Silva; Igor Otavio Minatel; Camila Renata Corrêa; Hector Alonzo Gomez Gomez; Giuseppina Pace Pereira Lima (MDPI AG, 2019)
Biogenic amines are important indicators of food quality with recognized antioxidant capacity. Diets that are rich in these compounds promote several benefits for human health, although the consumption in excess may result in food poisoning. This study aims to screen the levels of biogenic amines in four colored cauliflowers, before and after cooking (boiling, steaming, and microwaving). In addition, the levels of tryptophan and 5-hydroxytryptophan, two serotonin precursors, were analyzed. Our results reveal that thermal processing shows a tendency to increase tryptophan levels and reduce 5-hydroxytryptophan in colored cauliflowers. A reduction of the tryptophan and increase in serotonin contents in ‘Cheddar’, steamed or microwaved, was observed. A higher level of histamine was observed in the genotype ‘Forata’ after cooking, whereas melatonin levels were higher after steaming and microwaving. The lowest levels of biogenic amines and amino acids were observed in ‘Graffiti’. All the colored cauliflowers that were analyzed presented a chemical quality index (CQI) below the pre-established limits, indicating that are safe for consumption, even after cooking. We conclude that the levels of biogenic amines and amino acids in colored cauliflower are safe for human consumption and do not present health risks. Therefore, the consumption of these genotypes, raw or cooked, is a good source of bioactive compounds.